DIGITAL ENTREPRENEURSHIP LEARNING TRAINING WITH AI ENHANCING COMPETENCE AND PROFESSIONAL COMPETITIVENESS - Mukhtar, Saparuddin; Wibowo, Agus; Kusumaningrum, Alifah; Negara, Dwi Ringga Edwid Dian; Maulida, Ervina; Izza, Ashiilah Tsabit; Izzulhaq, Muhammad Zaki (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
Technological advancements, particularly in Artificial Intelligence (AI), have brought significant transformations to the field of entrepreneurship. AI can be utilized across various business domains, including market analysis, customer service automation, trend prediction, and digital marketing strategies. Nevertheless, many entrepreneurs, MSME actors, and professionals still lack sufficient knowledge and skills in applying AI to enhance their business competitiveness. Through a technology-driven approach, participants will gain insights into how AI can be employed to improve business efficiency, expand market reach, and foster more competitive innovations. This training program is designed for students, academics, and professionals seeking to develop digital competencies in business. The training materials cover AI applications in digital marketing, AI-based data analysis, smart business management strategies, and case studies on AI implementation in entrepreneurship.